Cell-free DNA BRAF V600E measurements during BRAF inhibitor therapy of metastatic melanoma: long-term analysis. Issue 3 (June 2020) - Kozak, Katarzyna; Kowalik, Artur; Gos, Aleksandra; Wasag, Bartosz; Lugowska, Iwona; Jurkowska, Monika; Krawczynska, Natalia; Kosela-Paterczyk, Hanna; Switaj, Tomasz; Teterycz, Paweł; Klimczak, Anna; Siedlecki, Janusz A.; et al.
Objective: We assessed the status of the BRAF V600E mutation in cell-free circulating tumor DNA (cfDNA) isolated from the plasma of patients with metastatic melanoma treated with the BRAF inhibitor vemurafenib, collected at different time points during therapy to evaluate the sensitivity and specificity of quantitative polymerase chain reaction and droplet digital polymerase chain reaction (ddPCR) and the correlation between the level of plasma cfDNA p.V600E and the long-term clinical outcome. Methods: cfDNA in patients with BRAF -mutated melanoma ( n = 62) was analyzed at baseline and at 4−8 weeks from the start of vemurafenib therapy. BRAF mutations were assessed using tumor tissue-derived DNA and circulating cfDNA from plasma samples. Quantification of BRAF V600E was performed in cfDNA using ddPCR. Results: cfDNA V600E was detected in the plasma of 48/62 (77%) patients at baseline and in 18/62 (29%) patients after 4–8 weeks of treatment. Patients positive for BRAF mutations in cfDNA at baseline had shorter progression-free survival (PFS) and overall survival (OS) compared with patients with undetectable cfDNA BRAF mutations. Undetectable cfDNA p.V600E at baseline and after 4–8 weeks of therapy was associated with the best prognosis. When treated as a continuous variable, the log-transformed concentration of baseline cfDNA p.V600E was significantly associated with both PFS and OS. This effect was retained in the multivariate OS Cox model adjusted for Eastern Cooperative Oncology Group performance status, the presence of brain metastases, patient age, and previous systemic treatment. Conclusions: Monitoring of plasma BRAF p.V600E cfDNA concentrations in patients with metastatic melanoma on targeted therapy may have prognostic value. Undetectable cfDNA p.V600E before and during treatment was associated with a favorable prognosis.